The community health worker as service extender, cultural broker and social change agent: a critical interpretive synthesis of roles, intent and accountability - Stephanie M Topp; Marta Schaaf; Lynn Freedman; Caitlin Warthin (BMJ Global Health)
This paper is a critical interpretive synthesis of community health workers (CHWs) and accountability in low-income and middle-income countries. The guiding questions were: What factors promote or undermine CHWs as accountability agents? (and) Can these factors be intentionally fostered or suppressed to impel health system accountability? We conducted an iterative search that included articles addressing the core issue of CHWs and accountability, and articles addressing ancillary issues that emerged in the initial search, such as ‘CHWs and equity.’CHWs are intended to comprise a ‘bridge’ between community members and the formal health system. This bridge function is described in three key ways: service extender, cultural broker, social change agent. We identified several factors that shape the bridging function CHWs play, and thus, their role in fomenting health system accountability to communities, including the local political context, extent and nature of CHW interactions with other community-based structures, health system treatment of CHWs, community perceptions of CHWs, and extent and type of CHW unionisation and collectivisation.Synthesising these findings, we elaborated several analytic propositions relating to the self-reinforcing nature of the factors shaping CHWs’ bridging function; the roles of local and national governance; and the human resource and material capacity of the health system. Importantly, community embeddedness, as defined by acceptability, social connections and expertise, is a crucial attribute of CHW ability to foment local government accountability to communities.